The outcome of bevacizumab treatment for diabetic macular oedema at the Charlotte Maxeke Johannesburg Academic Hospital - Hasrod, Irfaan (My University, 2018)
Aim: The aim of this study is to examine the outcomes of treatment of diabetic macular oedema using bevacizumab at Charlotte Maxeke Johannesburg Academic Hospital by analysing the change in visual acuity and a change in retinal macular thickness at three months following the first intravitreal bevacizumab injection. Method: A retrospective study of the records of all patients treated with intravitreal bevacizumab for diabetic macular oedema from 1st January 2013 to 31 December 2015 was done. Results: A total of 178 eyes (from 151 patients) were treated for diabetic macular oedema during the period of 1st January 2013 to 31st December 2015. Seventeen of these eyes were treated with 1 injection, 33 with 2 injections and 128 eyes with 3 injections from baseline to three months. From the patients who were treated with 3 injections, 80 completed treatment at three months and 48 went on to receive more injections. Thus dividing the eyes into 4 groups. Patients who received 1 injection showed no median change in VA, logMAR 1.0 interquartile range ”IQR” (0.6LogMAR; 2.0 LogMAR) at baseline to LogMAR 1.0 IQR (0.48logMAR; 2.0LogMAR) at three months. Patients who received 2 injections also showed no median change in VA, logMAR 0.77 IQR (0.6logMAR; 0.77logMAR) at baseline to logMAR 0.77 IQR (0.6logMAR; 1.0logMAR) at three months. Patients who received 3 injections showed an increase of visual acuity, LogMAR 0.77 IQR (0.6logMAR; 1.0logMAR) at baseline to logMAR 0.60 IQR (0.48logMAR; 0.77logMAR) at three months. The patients who received 3 injections at baseline and went on to receive further injections also showed an increase in median visual acuity, logMAR 0.77 IQR (LogMAR0.6; logMAR1.00) at baseline to logMAR 0.60 IQR (logMAR0.48; logMAR1.00) at three months. There was a decrease in macula thickness in all 4 groups. In patients receiving three injections at three months there was a significant p-value of 0.018 for thechange in macula thickeness from baseline of 313 micrometres IQR (256micrometres; 419micrometres) to three months of 266 micrometres IQR (219micrometres; 356micrometres). For patients who received three injections at three months but went on to receive further injections, a significant p-value of P=0.0061 for the change in macula thickness from baseline of 398 micrometres IQR (328micrometres; 452micrometres) to three months of 321 micrometres IQR (262micrometers; 387 micrometers). Conclusion: Bevacizumab is useful in the treatment of Diabetic macular oedema in terms of an increase in visual acuity and decrease in macular thickness, provided patients receive a loading dose of three intravitreal injections in the first three months of treatment.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Medicine in Ophthalmology, Johannesburg 2018
Keywords: Macular Edema; Bevacizumab; Intravitreal Injections